2018
DOI: 10.1139/cjc-2017-0329
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen evolution at conjugated polymer nanoparticle electrodes

Abstract: Organic polymer nanoparticles have been gaining attention in photovoltaics as a means to control the morphology of polymer composite films for the purpose of studying bulk heterojunction, photoactive layers. This work investigates the preparation of nanostructured organic thin films from P3HT:PC 61 BM nanoparticles and their characterization as photoelectrodes for the photoelectrochemical reduction of hydrogen in acidic solutions. The morphology and optoelectronic properties of the nanostructured photocathodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“… 29 37 Heterojunctions with donor and acceptor blending are another strategy to enhance charge separation, which has been widely studied in organic photovoltaics (OPVs). 38 , 39 However, to date, only few studies on heterojunction Pdots have been reported for hydrogen production, 32 , 40 , 41 which leaves room for exploration. Directions of interest include improving the stability for long-term use, 42 understanding the photocatalytic mechanism of heterojunction Pdots, and increasing the light absorption for more efficient sunlight conversion.…”
Section: Introductionmentioning
confidence: 99%
“… 29 37 Heterojunctions with donor and acceptor blending are another strategy to enhance charge separation, which has been widely studied in organic photovoltaics (OPVs). 38 , 39 However, to date, only few studies on heterojunction Pdots have been reported for hydrogen production, 32 , 40 , 41 which leaves room for exploration. Directions of interest include improving the stability for long-term use, 42 understanding the photocatalytic mechanism of heterojunction Pdots, and increasing the light absorption for more efficient sunlight conversion.…”
Section: Introductionmentioning
confidence: 99%
“…[58] Cheng et al also used the 5/PCBM film on a poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)-coated F-doped tin oxide (FTO) substrate to give the current of 45 µA cm −2 at 0 V versus RHE under Xe irradiation, and developed it with a Pt catalyst and the combination with IrO x water-oxidation counter electrode resulting in the solar-tofuel conversion efficiency of 0.12%. [59] Holdcroft et al [60] restated in their 2018 study of 5-film-based photocathodes, including its photoelectrochemical study using anthraquinone reduction as a proton-reduction model and observed hydrogen evolution on the 5/PCBM-nanoparticle film.…”
Section: Light-enhanced Hydrogen Production With π-Conjugated Polymers: Early Trials Using Conventional Polymers and High-performing Desimentioning
confidence: 99%
“…[43][44][45][46] The second architecture (architecture 2) incorporates an electrocatalyst (EC) for the HER (HER-EC) into the carbon semiconductor, which acts as light absorber. [47] The HER-EC acts as a cocatalyst with the carbon-based materials by lowering the HER activation energy of the latter, which significantly enhances the electrocatalytic activity. [47][48][49][52][53][54][55][56] The electron transfer between the light absorber and the EC specifically depends on the nature of the materials as well as on their mutual chemical-physical interaction.…”
Section: Evolution Of Photocathode Architectures Based On Carbon Semi...mentioning
confidence: 99%
“…[47] The HER-EC acts as a cocatalyst with the carbon-based materials by lowering the HER activation energy of the latter, which significantly enhances the electrocatalytic activity. [47][48][49][52][53][54][55][56] The electron transfer between the light absorber and the EC specifically depends on the nature of the materials as well as on their mutual chemical-physical interaction. [107] Therefore, the third architecture (architecture 3) incorporates CSLs in order to improve the electron transfer from the photactive material towards the EC.…”
Section: Evolution Of Photocathode Architectures Based On Carbon Semi...mentioning
confidence: 99%
See 1 more Smart Citation